Design of Public Opinion Monitoring Information System in Online Media - Pratama, Aryo; Ikhwan, Ali (Institute Of Advanced Knowledge and Science, 2024)
The Office of Communication and Information of North Sumatra has so far carried out the process of managing public information analysis manually using Microsoft Excel. This is of course less efficient considering the large number of incoming articles and the lack of data that may be out of sync. For this reason, an information system was created that can monitor public opinion in online media to facilitate the work of staff in carrying out the process of monitoring public opinion so that it is more efficient and effective so that it can improve service quality better. . This system is designed using Visual Studio Code as a text editor, PHP programming language as a web builder, Bootstrap as an interface design, and MySQL as a database on the system. This research produces a Public Opinion Monitoring Information System in Web-Based Online Media.